2004
DOI: 10.1002/tl.159
|View full text |Cite
|
Sign up to set email alerts
|

Student norms of classroom decorum

Abstract: Student perceptions of what constitutes appropriate and inappropriate classroom behavior are affected by who is being asked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Caboni, Hirschy, and Best (2004) investigated student attitudes towards their peers' uncivil behaviors in the classroom and the extent to which the students considered such behaviors to be acceptable. They found that "disrespectful disruptions," behaviors the authors defined as "active behavior in which a student engages that impedes learning by other members of the class" (p. 62) were not considered appropriate classroom behaviors.…”
Section: Overview Of Student Incivility In the Classroommentioning
confidence: 99%
“…Caboni, Hirschy, and Best (2004) investigated student attitudes towards their peers' uncivil behaviors in the classroom and the extent to which the students considered such behaviors to be acceptable. They found that "disrespectful disruptions," behaviors the authors defined as "active behavior in which a student engages that impedes learning by other members of the class" (p. 62) were not considered appropriate classroom behaviors.…”
Section: Overview Of Student Incivility In the Classroommentioning
confidence: 99%
“…Hirschy and Braxton derived specific examples of classroom incivilities from the formative research of Boice (1996) on this topic. Disrespectful disruptions are defined as active behavior in which a student(s) impedes the learning of their peers (Caboni, Hirschy, & Best, 2004). These include such behaviors as repeated interruptions of others during class, talking loudly to another student while someone else in the class is speaking, and receiving cell phone calls or text messages during class.…”
Section: Methodsmentioning
confidence: 99%
“…Behaviors such as coming to class high on drugs, sleeping during class, and coming to class intoxicated characterize insolent inattention. Insolent inattention is behavior that reflects a student' s lack of desire to learn or participate in classroom activities (Caboni, Hirschy, & Best 2004). Each of these types of incivilities gives students an opportunity to make judgments about the values, beliefs, and goals of their student peers.…”
Section: Methodsmentioning
confidence: 99%
“…Two broad categories of incivilities spring from the work of Boice (1996): disrespectful disruptions and insolent inattention (Caboni et al, 2004;. Disrespectful disruptions take the form of active behaviors by a student(s) that negatively influence the learning of other students in the class.…”
Section: Classroom Incivilitiesmentioning
confidence: 99%
“…Research tends to demonstrate that students espouse a normative pattern that proscribes insolent inattention, but not disrespectful disruptions (Caboni et al, 2004). Given the existence of a norm that rebukes insolent inattention by students, faculty members will encounter insolent inattention less frequently than disrespectful disruptions.…”
Section: Classroom Incivilitiesmentioning
confidence: 99%